The Effect of Pb Dopant on The Critical Temperature of BSCCO-2212 Superconducting Crystal - . Nurmalita (Syiah Kuala University, 2012)
A reseach about the study on the critical temperature of BSCCO-2212 superconducting crystal with slow cooling periode of 90 hours objected for knowing the critical temperature of superconducting crystal. An experiment has been carried out on the formation of BSCCO-2212 superconducting crystal by the melt-textured growth at 9300C. The syntheses were conducted with the molar ratio of the Pb dopant varied between 0 and 0.4 , while the period of the slow cooling process fixed at 90 hours. Characterization of samples with the curve R-T that sample with Pb dopant ratio 0 has the highest critical temperature of 60K and sample with Pb dopant ratio 0.2 and 0.4 has the critical temperature of 57K and 52K respectively